PERAN GURU TERHADAP PERKEMBANGAN KARAKTER ANAK USIA DINI DI PAUD TKIT NURALIMA - Lestary Alammy, Lenny; Arifudin, Opan; Chusnarin Haryanti, Heny (Penerbit Lafadz Jaya, 2025)
Indonesia is currently facing a moral crisis, making character education from an early age an urgent necessity. Teachers hold a strategic role in this process, not only as educators but also as role models, mentors, motivators, evaluators, and partners of parents. This study aims to describe the role of teachers in shaping the character of early childhood students at PAUD TKIT Nuralima, Majalaya District, Karawang Regency. A descriptive qualitative method was employed, with data collected through observations, interviews, and documentation involving the principal and teachers as research subjects. Data were analyzed through the stages of reduction, presentation, and conclusion drawing, while data validity was tested using triangulation techniques. The findings reveal that teachers consistently perform their roles in character formation. As role models, teachers habituate children to practice religious values, use polite language, and dress modestly. As mentors, teachers guide children toward independence through daily routines such as taking off shoes, arranging bags, and praying before lessons. Their role as motivators is evident in the use of praise and simple rewards, while evaluation is carried out through observations and progress notes. Collaboration with parents further strengthens the success of character education. In conclusion, the teacher’s role is highly significant and aligns with the competencies stated in Regulation of the Minister of National Education No. 16 of 2007, as well as the national education goals outlined in Law No. 20 of 2003. The implication is that strengthening the teacher’s role and school–parent collaboration is the key to successful early childhood character education. education.